2020
DOI: 10.1002/chem.201904744
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Magneto‐Structural Features of the Halo‐Substituted Materials [FeIII(5‐X‐salMeen)2]Y: a Cooperative [HS‐HS]↔[HS‐LS] Spin Transition

Abstract: X‐ray structures of the halo‐substituted complexes [FeIII(5‐X‐salMeen)2]ClO4 (X=F, Cl, Br, I) [salMeen=N‐methyl‐N‐(2‐aminoethyl)salicylaldiminate]at RT have revealed the presence of two discrete HS complex cations in the crystallographic asymmetric unit with two perchlorate counter ions linking them by N−Hamine⋅⋅⋅Operchlorate interactions. At 90 K, the two complex cations are distinctly HS and LS, a rare crystallographic observation of this coexistence in the FeIII‐salRen (R=alkyl) spin‐crossover (SCO) system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…The magnetic measurements are consistent with the two-step SCO from a [LS-LS] to a [LS-HS] and [HS-mHS] state observed by X-ray crystallography. The SCO profile of 2 ·0.5hexane also reveals two-step SCO with a hysteresis of 60 K from 240 to 300 K. However, even at 50 K χ M T is 1.0 cm 3 K mol –1 , much higher than expected for LS Fe III . ,, At 350 K, χ M T is 3.9 cm 3 K mol –1 , slightly lower than expected for the full HS state. ,, The results mirror the findings from the structural studies, where a SCO from a [LS-HS] state to a [LS-MS] state is observed. The remaining compounds were explored by VSM with χ M T values between 0.4 and 0.7 cm 3 K mol –1 between 50 and 350 K being consistent with the LS state observed crystallographically (Figure S7).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The magnetic measurements are consistent with the two-step SCO from a [LS-LS] to a [LS-HS] and [HS-mHS] state observed by X-ray crystallography. The SCO profile of 2 ·0.5hexane also reveals two-step SCO with a hysteresis of 60 K from 240 to 300 K. However, even at 50 K χ M T is 1.0 cm 3 K mol –1 , much higher than expected for LS Fe III . ,, At 350 K, χ M T is 3.9 cm 3 K mol –1 , slightly lower than expected for the full HS state. ,, The results mirror the findings from the structural studies, where a SCO from a [LS-HS] state to a [LS-MS] state is observed. The remaining compounds were explored by VSM with χ M T values between 0.4 and 0.7 cm 3 K mol –1 between 50 and 350 K being consistent with the LS state observed crystallographically (Figure S7).…”
Section: Resultssupporting
confidence: 77%
“…Selected bond lengths and octahedral distortion parameters, calculated using OctaDist, are given in Table . Complex 1· 0.5hexane was studied at 150 K, 263 K (two cycles), and 340 K, where Fe1 undergoes SCO (ΔFe–N/O av\ = 0.07 Å, ΔΣ = 16.0°, and ΔΘ = 66.5°) at 263 K followed by Fe2 (ΔFe–N/O av = 0.07 Å, ΔΣ = 28.5°, and ΔΘ = 93.0°) at 340 K. ,, Hence, 1· 0.5hexane exhibits a two-step SCO from [LS-LS] to [LS-HS] and [HS-mHS] (mHS = mostly high spin).…”
Section: Resultsmentioning
confidence: 99%
“…This allows for the modulation of the intrinsic properties of these crystals, such as optical, redox, electrical conductivity, catalytic, and, in particular, the spin crossover (SCO) properties. The spin state of the complex is highly dependent on the crystal field splitting energy of the e g and t 2g orbitals and the intraorbital electron-pairing energy. , Stimuli-responsive SCO with abrupt, stepped, or hysteretic spin-switching mechanisms displaying binary or even ternary functionality can be controlled through perturbations in temperature, pressure, and light. , Tuning the magnetic properties of these materials has proven to be a significant challenge as they rely on cooperative effects extending through a crystal lattice. The presence of guest molecules can significantly perturb SCO behavior resulting in substantial changes in cooperativity and T 1/2 . Molecular crystalline materials comprising discrete components typically lose crystallinity upon guest removal .…”
Section: Introductionmentioning
confidence: 99%
“…2 Isomorphous families of compounds are particularly useful in that regard, in showing how small structure changes can influence the temperature and cooperativity of a thermal spin transition within the same crystal lattice structure. 3 While some groups of isomorphous compounds exhibit very consistent SCO behaviour, [4][5][6] in other cases a surprising variation in the cooperativity or occurrence of SCO is observed. [7][8][9][10][11] We recently described the solvate crystals [FeL 2 ]X 2 ÁMe 2 CO (1X 2 Á Me 2 CO, Scheme 1; L = N-(2,6-di{pyrazol-1-yl}pyrid-4-yl)acetamide; X À = BF 4 À or ClO 4 À ).…”
mentioning
confidence: 99%